Airborne observations of bioaerosol over the Southeast United States using a Wideband Integrated Bioaerosol Sensor. Issue 14 (21st July 2016) - Ziemba, Luke D.; Beyersdorf, Andreas J.; Chen, Gao; Corr, Chelsea A.; Crumeyrolle, Suzanne N.; Diskin, Glenn; Hudgins, Charlie; Martin, Robert; Mikoviny, Tomas; Moore, Richard; Shook, Michael; Thornhill, K. Lee; et al.
Abstract: Biological aerosols represent a diverse subset of particulate matter that is emitted directly to the atmosphere in the form of (but not limited to) bacteria, fungal spores, pollens, viruses, and plant debris. These particles can have local air quality implications, but potentially play a larger climate role by acting as efficient ice nucleating particles (INPs) and cloud condensation nuclei. We have deployed a Wideband Integrated Bioaerosol Sensor on the NASA DC‐8 aircraft to (1) quantify boundary layer (BL) variability of fluorescent biological aerosol particle (FBAP) concentrations in the Southeast United States (SEUS), (2) link this variability explicitly to land cover heterogeneity in the region, and (3) examine the vertical profile of bioaerosols in the context of convective vertical redistribution. Flight‐averaged FBAP concentrations ranged between 0.1 and 0.43 scm −3 (cm −3 at standard temperature and pressure) with relatively homogeneous concentrations throughout the region; croplands showed the highest concentrations in the BL (0.37 scm −3 ), and lowest concentrations were associated with evergreen forests (0.24 scm −3 ). Observed FBAP concentrations are in generally good agreement with model parameterized emission rates for bacteria, and discrepancies are likely the result of fungal spore contributions. Shallow convection in the region is shown to be a relatively efficient lofting mechanism as the vertical transport efficiency of FBAP is at least equal to black carbon aerosol, suggesting that ground‐level FBAP survives transport into the free troposphere to be available for INP activation. Comparison of the fraction of coarse‐mode particles that were biological ( f FBAP ) suggested that the SEUS ( f FBAP = 8.5%) was a much stronger source of bioaerosols than long‐range transport during a Saharan Air Layer (SAL) dust event ( f FBAP = 0.17%) or summertime marine emissions in the Gulf of Mexico ( f FBAP = 0.73%). Key Points: The southeast USA region is a significant source of bioaerosols Shallow convection allows vertical transport of bioaerosols Emission rates from different land types are relatively homogeneous